MULTICULTURAL SCHOOL CULTURE: MEDIA TO INSTILL THE VALUES OF RELIGIOUS MODERATION IN PRIMARY SCHOOLS - Fita Mustafida; Muhammad Sulistiono; Abd. Gafur (PD PGMI se Indonesia, 2025)
Multicultural school culture plays an important role in shaping the character of tolerant and moderate students in the midst of diversity. This study aims to analyze the cultural forms of multicultural schools that support the cultivation of religious moderation values in elementary schools. A qualitative approach with case study types is used to produce comprehensive research. Data collection techniques used participant observation, in-depth interviews, and documentation. The results of the study show that there are three main forms of multicultural school culture that contribute to instilling the value of religious moderation, namely: (1) democratic culture; provide space for student participation, deliberation, and procedural justice; (2) positive social culture; building relationships based on trust, mutual respect, and solidarity; and (3) child-friendly culture; ensuring physical, psychological, and social security as a prerequisite for active participation. These three cultures complement each other and form an inclusive-multiculturalist education ecosystem, so that a multicultural value-based school culture is important as a systemic and transformative strategy in an effort to implement character education to strengthen religious moderation for elementary school students. This paper recommends strengthening school policies that support the systematic and collaborative implementation of multicultural culture between schools, families, and communities for the development of multicultural school culture as a medium to strengthen religious moderation. These findings are expected to be a reference for the development of multicultural education models and the strengthening of effective religious moderation, especially at the basic education level.